2017
DOI: 10.1038/tpj.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

Sulfotransferase 1A3/4 copy number variation is associated with neurodegenerative disease

Abstract: The cytosolic aryl sulfotransferase genes SULT1A3 and SULT1A4 are located on chromosome 16p11.2 in a region of chromosomal instability. SULT1A3/4 are important enzymes in the metabolism of catecholamines linked to neurodegenerative diseases such as Parkinson's and Alzheimer's. In the present study, copy number variation of the SULT1A3/4 genes in healthy individuals, as well as a cohort of Parkinson's disease and Alzheimer's disease patients was examined. In all subjects, SULT1A3/4 copy number varied from 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…SULT1A3 is a protein-coding gene related to sulfotransferase enzymes that catalyze the sulfate conjugation of many hormones and neurotransmitters. It has been found that Alzheimer's subjects have a significant lower SULTA13 copy number compared to healthy controls [24]. Induction of SULTA13 significantly protects cells from dopamine neurotoxicity.…”
Section: Vs Healthy Controls Classificationmentioning
confidence: 99%
“…SULT1A3 is a protein-coding gene related to sulfotransferase enzymes that catalyze the sulfate conjugation of many hormones and neurotransmitters. It has been found that Alzheimer's subjects have a significant lower SULTA13 copy number compared to healthy controls [24]. Induction of SULTA13 significantly protects cells from dopamine neurotoxicity.…”
Section: Vs Healthy Controls Classificationmentioning
confidence: 99%
“…A number of the identified genes such as ACAT1 (Table 1 ) and SGIP1 (Table 2 ) confer risk for diseases or endophenotypes that are predominantly specific to the human species, such as complex psychiatric disorders [ 46 , 47 ]. SULT1A4 (Table 1 ) plays a critical role in neurotransmitter metabolism in the human brain and is also linked to neurodegeneration [ 48 ]. APOA2 (Additional file 4 ) along with several other lipoproteins is linked to cognitive health [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…NVL), confer risk for diseases that are predominantly specific to the human species, such as schizophrenia and bipolar disorder (Wang et al 2015). Neurodegeneration is another example linked to genes such as SULT1A3 (Butcher et al 2017). In another remarkable example, TBR1 is involved in FOXP2 gene expression, which has pivotal role in speech and language in human (Becker et al 2018).…”
Section: Discussionmentioning
confidence: 99%